New Insights into Intestinal Permeability in Irritable Bowel Syndrome-Like Disorders: Histological and Ultrastructural Findings of Duodenal Biopsies - Selenia Miglietta; Raffaele Borghini; Michela Relucenti; Veronica Sorrentino; Rui Chen; Xiaobo Li; Francesco Fazi; Giuseppe Donato; Giuseppe Familiari; Vincenzo Petrozza; Antonio Picarelli (Cells, 2021)
Background and Aim: Diarrhea, abdominal pain, and bloating are frequent in irritable bowel syndrome (IBS)-like disorders, although little is known about their intestinal ultrastructural alterations. The aim of the present study was to study duodenal biopsies from IBS-like patients to find ultrastructural alterations. Materials and Methods: Study design: descriptive comparative pilot study. Thirty outpatients (9 male and 21 female; median age 37.7 years; range, 20 to 65 years) complaining of IBS-like symptoms were enrolled between January 2015 to May 2019 and were divided into 6 groups, each equally consisting of 5 patients: (A) untreated celiac disease (uCD); (B) treated celiac disease (tCD); (C) wheat allergy (WA); (D) Non-celiac gluten sensitivity (NCGS); (E) Nickel allergic contact mucositis (Ni ACM); (F) controls affected by GERD. Transmission electron microscopy (TEM) morphological characteristics were: microvilli length, intermicrovillar distance, junctional complexes (JC) gap width, autophagic bodies, apoptosis, altered mitochondria, lipid/chylomicron droplets, and mast cells. Regarding JC, we focused on tight junctions (TJ), adherens junctions (AJ), and desmosomes. Results: Major alterations in microvilli length and intermicrovillar distance have been observed in the subjects affected by uCD. Microvilli of tCD patients showed marked recovery after adequate GFD, although not comparable to controls. Intermediate microvillar alterations were instead observed in NCGS and Ni ACM, while characteristics of WA subjects appeared more similar to tCD. Regarding JC, TJ did not show significant differences between all groups studied, including controls. The AJ were significantly more dilated in all groups compared to controls, while no significant differences were found between the pathological groups. The distance between desmosomes was greater in uCD, NCGS, and Ni ACM than in tCD, WA, and controls. Finally, intracellular alterations have been detected in most of the groups studied although they seemed more unspecific. Conclusions: TEM analysis confirmed damages to the intestinal barrier and defense mechanisms by enterocytes in IBS-like patients, probably linked to low-grade inflammation or adverse reactions triggered by food allergens, heavy metals, or other unknown. On the other hand, our study needs confirmation and further investigations with larger populations to facilitate diagnosis, therapy, and prevention of IBS-like disorders in the future.